Participatory evaluation. What is it? Why do it? What are the challeng es? - Zukoski, A.; Luluquisen, Mia (Community-based public health policy & practice, 2002)
Yogi Berra was right when he remarked, “If you don’t know where you’re going, you’ll wind up somewhere else.” When we collectively apply our hopes and energies to improving our communities, how do we know if we ’re making the right choices along the way? How will we notice when we are spinning our wheels and what changes to make? How will we know th at we are making a difference? And how will we know what success looks like to everyone in the group? By taking a community-based public hea lth approach to our work, we create an opportunity to engage in a part icular type of evaluation—participatory evaluation – that can help ans wer those questions. For those groups that are interested in this appr oach, this policy brief discusses the key concepts of participatory ev aluation and some tips for applying it. We also present some real-life examples from two evaluators who work with grantees of the Partnershi p for the Public’s Health Initiative.